An innovative emergency transportation scenario for mass casualty incident management: Lessons learnt from the Formosa Fun Color Dust explosion. Issue 11 (19th March 2021) - Lin, Ming-Wei; Pan, Chih-Long; Wen, Jet-Chau; Lee, Cheng-Haw; Wu, Zong-Ping; Chang, Chin-Fu; Chiu, Chun-Wen
Abstract : Abstract: The purpose of this research is to analyze and introduce a new emergency medical service (EMS) transportation scenario, Emergency Medical Regulation Center (EMRC), which is a temporary premise for treating moderate and minor casualties, in the 2015 Formosa Fun Color Dust Party explosion in Taiwan. In this mass casualty incident (MCI), although all emergency medical responses and care can be considered as a golden model in such an MCI, some EMS plans and strategies should be estimated impartially to understand the truth of the successful outcome. Factors like on-scene triage, apparent prehospital time ( app PHT), inhospital time (IHT), and diversion rate were evaluated for the appropriateness of the EMS transportation plan in such cases. The patient diversion risk of inadequate EMS transportation to the first-arrival hospital is detected by the odds ratios (ORs). In this case, the effectiveness of the EMRC scenario is estimated by a decrease in app PHT. The average app PHTs (in minutes) of mild, moderate, and severe patients are 223.65, 198.37, and 274.55, while the IHT (in minutes) is 18384.25, 63021.14, and 83345.68, respectively. The ORs are: 0.4016 (95% Cl = 0.1032–1.5631), 0.1608 (95% Cl = 0.0743–0.3483), and 4.1343 (95% Cl = 2.3265–7.3468; P < .001), respectively. The app PHT has a 47.61% reduction by employing an EMRC model. Due to the relatively high app PHT, diversion rate, and OR value in severe patients, the EMS transportation plan is distinct from a prevalent response and develops adaptive weaknesses of MCIs in current disaster management. Application of the EMRC scenario reduces the app PHT and alleviates the surge pressure upon emergency departments in an MCI.